Производственный инвентарь участка культурного слоя на юг от первого межиричского жилища Production Inventory of area of cultural layer to the south from the first mezhyrichian dwelling - Шидловский, П.С.; Нужный, Д.Ю.; Пеан, С. (Археологический альманах, 2014)
В данной статье представлены материалы последних исследований участка «топталища» относящегося к первому хозяйственно-бытовому комплексу верхнепалеолитической стоянки Межирич, основное внимание уделяется анализу кремневого инвентаря. Mezhyrich is well-known Upper Palaeolithic settlement which was excavated since 1966 by different groups of researchers. Previous investigators discovered 4 dwellings made from mammoth bones and tusks, as well as pits around each of them. Present excavations concentrated on the investigations of different objects which are connected with 1st and 2nd dwellings, such as work-shops, pits and parts of cultural layer saturated by artefacts and bone fragments – so called “toptalische”. Among the objects that investigated last time is the south section of the 1st dwelling – excavated in 1966 by I.G. Pidoplichko – the area of high activity connected to the entrance to the dwelling. This article presents the analysis of inventory that comes from this area and the main attention gives to flint artefacts. Based on the typological analysis the authors emphasize the clear difference between statistic data of flint artefatcs that comes from the dwelling and that from mentioned area of “toptalische”. The assemblages from different objects of Mezhyrich settlement demonstrate a certain diversity of main typological indexes, what recognized as the evidence of various kinds of activity carried out in different parts of the site.